2007
DOI: 10.1108/02686900710759389
|View full text |Cite
|
Sign up to set email alerts
|

The impact of codes of ethics and experience on auditor judgments

Abstract: PurposeThe purpose of this study is to investigate the impact of the presence of a code of ethics on the quality of auditors' judgments, within the context of the new International Standard on Quality Controls 1 (ISQC1).Design/methodology/approachA sample of 112 professional accountants and auditing students was employed to investigate the effect of the presence of a code of ethics (operationalised as the presence vs absence of an organisational code of conduct) on the quality of audit judgments, pertaining to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
72
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 43 publications
(71 reference statements)
9
72
0
5
Order By: Relevance
“…And also the question about whether a published code of ethics has any impact on accounting professionals' ethical judgments has produced a mixed response (Pflugrath et al, 2007). For example, Herron and Gilbertson (2004) found that the AICPA principles-based ethical codes do not effectively promote American accounting students' independence judgments especially where they apply lower levels of moral development.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…And also the question about whether a published code of ethics has any impact on accounting professionals' ethical judgments has produced a mixed response (Pflugrath et al, 2007). For example, Herron and Gilbertson (2004) found that the AICPA principles-based ethical codes do not effectively promote American accounting students' independence judgments especially where they apply lower levels of moral development.…”
Section: Introductionmentioning
confidence: 99%
“…Only limited research (e.g., Pflugrath et al, 2007;Herron and Gilbertson, 2004) has examined codes of ethics within the accounting profession although Jones et al (2003) suggested the role of codes of ethics in auditors' ethical decision making deserves further attention.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations